1977
DOI: 10.1017/s003329170000636x
|View full text |Cite
|
Sign up to set email alerts
|

Previous occupational stability as a predictor of employment after psychiatric rehabilitation

Abstract: SynopsisSeveral indices of occupational stability are discussed and the importance of controlling for age in assessing occupational stability emphasized. The ability of 6 indices to predict the stable resettlement of psychiatric patients at work after a course of rehabilitation was examined. Though mean job length was a significant predictor, indices based on change of occupation rather than change of job were more successful. Stable resettlement at work was related to how much time people had spent in long jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Wilson et al, (1969) found more neurotics than psychotics to be employed at follow-up. While this neurotic/psychotic comparison might be expected to hold in other studies, neither Sturm and Lipton (1967) nor Watts and Bennett (1977) uncovered a relationship between the psychotic/nonpsychotic classification and employment.…”
Section: Nine Major Findingsmentioning
confidence: 59%
See 1 more Smart Citation
“…Wilson et al, (1969) found more neurotics than psychotics to be employed at follow-up. While this neurotic/psychotic comparison might be expected to hold in other studies, neither Sturm and Lipton (1967) nor Watts and Bennett (1977) uncovered a relationship between the psychotic/nonpsychotic classification and employment.…”
Section: Nine Major Findingsmentioning
confidence: 59%
“…Because no consistent relationship was found between psychiatric symptoms and vocational performance, it would seem that there would also be no relationship between diagnosis and future vocational performance. A number of studies have confirmed the absence of such a relationship (Distefano & Pryer, 1970;Douzinas & Carpenter, 1981;Ethridge, 1968;Goss & Pate, 1967;Hall, Smith, &Skimkunas, 1966;Lorei, 1967;Moller etal., 1982;Sturm & Lipton, 1967;Watts & Bennett, 1977).…”
Section: Nine Major Findingsmentioning
confidence: 99%
“…The question of whether a relationship exists between diagnosis and future work performance is equally puzzling. Anthony and Jansen (1984) cited a num ber of studies demonstrating the ab sence of such a relationship (Moller et al, 1982;Sturm & Lipton, 1967;Watts & Bennett, 1977), in their review of pre dictors of vocational capacity. However, recent reviews present variable and con flicting results.…”
Section: Revealed Significant Group Differences Along the Dimensions ...mentioning
confidence: 99%
“…Research workers have, therefore, been particularly interested in the effect of psychiatric disorders on work and return to work (e.g. Watts & Bennett, 1977). There have been a few reports of the adverse effects of unemployment on male mental health (Kasl et al 1975;Catalano & Dooley, 1977).…”
Section: Employment Statusmentioning
confidence: 99%